Statin Decreases Helicobacter pylori Burden in Macrophages by Promoting Autophagy - Liao, Wei-Chih; Huang, Mei-Zi; Wang, Michelle Lily; Lin, Chun-Jung; Lu, Tzu-Li; Lo, Horng-Ren; Pan, Yi-Jiun; Sun, Yu-Chen; Kao, Min-Chuan; Lim, Hui-Jing; Lai, Chih-Ho (Frontiers in Cellular and Infection Microbiology, 2017)
Statins, 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase inhibitors, have been found to provide protective effects against several bacterial infectious diseases. Although the use of statins has been shown to enhance antimicrobial treated Helicobacter pylori eradication and reduce H. pylori-mediated inflammation, the mechanisms underlying these effects remain unclear. In this study, in vitro and ex vivo macrophage models were established to investigate the molecular pathways involved in statin-mediated inhibition of H. pylori-induced inflammation. Our study showed that statin treatment resulted in a dose-dependent decrease in intracellular H. pylori burden in both RAW264.7 macrophage cells and murine peritoneal exudate macrophages (PEMs). Furthermore, statin yielded enhanced early endosome maturation and subsequent activation of the autophagy pathway, which promotes lysosomal fusion resulting in degradation of sequestered bacteria, and in turn attenuates interleukin (IL)-1β production. These results indicate that statin not only reduces cellular cholesterol but also decreases the H. pylori burden in macrophages by promoting autophagy, consequently alleviating H. pylori-induced inflammation.